Proteomic Study of Fetal Membrane: Inflammation-Triggered Proteolysis of Extracellular Matrix May Present a Pathogenic Pathway for Spontaneous Preterm Birth - Pan, Jing; Tian, Xiujuan; Huang, Honglei; Zhong, Nanbert (Frontiers in Physiology, 2020)
Introduction: Spontaneous preterm birth (sPTB), which predominantly presents as spontaneous preterm labor (sPTL) or preterm premature rupture of fetal membrane (PPROM), is a syndrome that accounts for 5-10% of live births annually. The long-term morbidity in surviving preterm infants is significantly higher than that in full-term neonates. The causes of sPTB are complex and not fully understood. Human placenta, the maternal and fetal interface, is an environmental core of fetal intrauterine life, mediates fetal oxygen exchange, nutrient uptake, and waste elimination and functions as an immune-defense organ. In this study, the molecular signature of preterm birth placenta was assessed and compared to full-term placenta by proteomic profiling. Material and methods: Four groups of fetal membranes (the amniochorionic membranes), with five cases in each group in the discovery study and 30 cases in each group for validation, were included: groups A: sPTL; B: PPROM; C: full-term birth (FTB); and D: full-term premature rupture of membrane (PROM). Fetal membranes were dissected and used for proteome quantification study. Maxquant and Perseus were used for protein quantitation and statistical analysis. Both fetal membranes and placental villi samples were used to validate proteomic discovery. Results: Proteomics analysis of fetal membranes identified 2,800 proteins across four groups. Sixty-two proteins show statistical differences between the preterm and full-term groups. Among these differentially expressed proteins are 1) proteins involved in inflammation (HPGD), T cell activation (PTPRC), macrophage activation (CAPG, CD14, and CD163), 2) cell adhesion (ICAM, ITGAM), 3) proteolysis (CTSG, ELANE, and MMP9), 4) antioxidant (MPO), 5) extracellular matrix (ECM) proteins (APMAP, COL4A1, LAMA2, LMNB1, LMNB2, FBLN2, and CSRP1) and 6) metabolism of glycolysis (PKM, ADPGK), fatty acid synthesis (ACOX1, ACSL3), and energy biosynthesis (ATP6AP1, CYBB). Conclusion: Our molecular signature study of preterm fetal membranes revealed inflammation as a major event, which is inconsistent with previous findings. Proteolysis may play an important role in fetal membrane rupture. ECMs have been altered in preterm fetal membranes due to proteolysis. Metabolism was also altered in preterm fetal membranes. The molecular changes in the fetal membranes provided a significant molecular signature for PPROM in preterm syndrome.